Analysis of Students Thinking Skills In English Language Classroom: Students’ Perceptions - Zahratul Aeni; Ika Harianingsih; Zurina Khairuddin (Publikasi Indonesia, 2022)
The advancement of education in the twenty-first century is now confronted with significant challenges. Accordingly, it is essential to train students to think critically. Moreover, thinking creatively and critically will have a significant impact on preparing future generations. This study was conducted as a result of observations revealed that students struggle with learning activities when teachers integrate the thinking skills process in the classroom. The purpose of this study is to examine students' perceptions of the integration of thinking skills theory in English language classroom. The research method applied in this study is quantitative. The data were collected by distributing the questionnaire to 30 students in grade 9 at the secondary school level. Through the descriptive statistical analysis, the calculation of the mean and std. Deviation confirmed “very high” and “high” responses out of 14 questions based on the mean Interval Score Interpretation proposed by Kinay and Ardıç (2017). It indicated that students positively perceive the use of thinking skills in English language classrooms. This study concludes that integrating thinking skills in English language classroom could develop students’ critical thinking.